Bio-hydrogen Production From Vinasse By Using Agent Fermentation Of Photosynthetic Bacteria Rhodobium marinum - Nusaibah - Nusaibah; Khaswar - Syamsu; Dwi - Susilaningsih (Research Centre of Inorganic Materials and Complexs, 2020)
The aim of this research was to find out the effect of substrate concentrations (COD) of vinasse and the length of fermentation time to bio-hydrogen gas production using agent fermentation of photosynthetic bacteria, Rhodobium marinum. The production of bio-hydrogen was examined by varying COD of vinasse (10,000; 20,000; 30,000; 40,000; 50,000 mg COD/L) at certain fermentation time in the third, sixth and ninth day. The highest Hydrogen gas was obtained at ninth day of fermentation (82.66±18.6 mL). The highest Hydrogen Production Rate (HPR) and COD removal rate were obtained at concentration 50,000 mg COD/L, namely 109.98 mL H2/L/d and 1437.66 mg COD/L/d, respectively. Thus it can be concluded, the concentration of substrates (COD) from vinasse and the length of fermentation time have an effect on production of bio-hydrogen gas using Rhodobium marinum